EVALUASI SISTEM PEMBELAJARAN BLENDED LEARNING BERBASIS MODEL UTAUT DI JURUSAN TEKNIK INFORMATIKA DAN KOMPUTER, UNIVERSITAS NEGERI MAKASSAR - Fadhlirrahman Baso; Nur Azizah Ayu Safanah; Ahmad Faris Al Faruq; Ardi Ansya; Andi Muh Achyar AM (Sakura Digital Nusantara, 2023)
Blended learning is a response to government policy that seeks to establish a new normalcy of life. Blended learning is one of the innovative learning methods where students are introduced to the concept of combining face-to-face learning in class and online learning. Therefore, the purpose of this study is to assess the blended learning system that was examined using the UTAUT model. This research uses a quantitative approach with descriptive research methods. This study included 61 majoring in informatics and computer engineering students from Makassar State University. Data was obtained by data collection techniques in the form of questionnaires distributed through the google form. The instrument in the form of a research questionnaire with data collection techniques and then analyzing questionnaires distributed through Google forms was carried out using a Likert scale to obtain research results. It is known that the blended learning model has a good influence on the learning process.